Correlation of the Expression of Vascular Endothelial Growth Factor with Clinical Staging and Outcome in Patients Affected with Colorectal Carcinoma: A Study from Uganda - Wismayer, Richard; Kiwanuka, Julius; Jombwe, Josephat; Elobu, Emmanuel; Wabinga, Henry; Odida, Michael (Medicine and Medical Research: New Perspectives Vol. 2, 2024)
Introduction: Invasion and metastasis are the most life-threatening aspects of the colorectal neoplastic process. Many studies have shown that invasion, metastasis, and solid tumour growth are dependent on new blood vessel formation from established vasculature. According to data from the Kampala Cancer Registry in Uganda, the number of instances of colorectal cancer (CRC) has increased in this area, and patients are presenting at an advanced stage and younger ages. A relationship between tumour growth, distant metastasis, and a poor prognosis with an increased expression of VEGF has been reported in studies. Aim: The aim of this study was to analyse the correlation of VEGF with the clinicopathological characteristics of Ugandan patients with colorectal cancer. Methods: Immunohistochemistry was carried out on fifty-two patients’ paraffin-embedded tissue blocks of CRC between 2008–2021. VEGF expression was detected using the indirect immunoperoxidase method which used monoclonal antibody VEGF, DAKO Agilent USA, Clone VG1, and reference M7273. The haematoxylin and eosin stains were used to evaluate the grade, lymphovascular invasion status, and histopathological subtypes of CRC. The demographic data, staging, and topography of the tumours were obtained from the clinical patients’ files and the Kampala Cancer Registry. The biopsy specimens were obtained during colonoscopy and the resected colorectal specimens at operation. Using a standard pretested Data Extraction Form, data for all tissue samples was extracted from the clinical patients’ files in the respective hospitals and the Kampala Cancer Registry. Results: Out of fifty-two CRC participants, there were 7(43.7%) participants with stage IV disease compared to 2(12.5%) with stage I disease and this reached statistical significance (p=0.0479). There were 11(68.8%) participants with grade II disease compared to 2(12.5%) with grade I disease from those that stained positively for VEGF (p=0.0012). Classical adenocarcinoma constituted 13(81.3%) participants compared to 3(18.8%) mucinous adenocarcinomas and signet ring colorectal carcinoma from those that stained positively for VEGF (p=0.0000). CRC grading was negatively correlated with VEGF-1 expression (r=-0.0565) (p=0.7091). The mechanism responsible for increasing the results of chemotherapy with anti-VEGF therapy is not entirely understood. However, tumour apoptosis may be increased with the inhibition of angiogenesis. Conclusions: There was a tendency to increase the expression of VEGF with increasing stages of CRC. A poor prognosis and increased VEGF-1 expression were substantially correlated with the existence of metastases. More effective medical interventions for colorectal cancer in Uganda are required, utilizing chemotherapy and anti-VEGF drug combinations.